Involvements of Nrf2 and oxidative stress in the ozone-elicited exacerbation in an allergic rhinitis model - Na Sun; Yu Huang; Xueyan Zhang; Yue Niu; Yusen Duan; Haidong Kan; Ruxin Zhang (Ecotoxicology and Environmental Safety, 2023)
Objective and design: An experimental rat allergic rhinitis(AR) model was made to explore the effect of different concentrations of ozone exposure and evaluate the roles of nuclear factor erythroid 2-related factor 2(Nrf2) and oxidative stress in ozone exposure. Method: Sprague-Dawley rats were sensitized with ovalbumin (OVA). Three groups of AR rats were exposed respectively to different concentrations of ozone for 2 h on 6 weeks. Nasal symptoms and OVA- specific Ig E in the serum were evaluated. The pathological changes in the nasal mucosa were examined. Malondialdehyde (MDA) level and activity of superoxide dismutase(SOD) and glutathione peroxidase (GSH-Px,GPX) in the nasal mucosa tissue were measured through a spectrophotometry-based method. Nrf2、Kelch-1ike ECH- associated protein-l (Keap1) proteins was measured by western blotting. GPX1、GPX2 mRNA were detected by quantitative real time-PCR(qRT-PCR). Results: Our results showed that ozone exposure induced a significant increase of the number of sneezes, nasal rubs, amount of nasal secretion and OVA-sIgE in the serum of AR model. Ozone effected oxidative stress in different concentration. The content of MDA in AREH group was significantly higher than AR groups. The activities of SOD and GSH-Px in nasal mucosa showed different trends in different concentration groups. The activities of SOD and GSH-Px in AREL and AREM groups were higher than AR group, but decreased at AREH group. The nucleoprotein level of Nrf2 in AREL and AREM groups was higher than AR groups. However, in AREH group, it was significantly decreased, compared with AREL and AREM groups. GPX1 and GPX2 mRNA levels in nasal mucosa showed the same trend in different exposure groups. Conclusions: Different concentrations of ozone inhalation causes changes of the expression of Nrf2 nuclear protein and its target genes in nasal mucosa of AR. High concentration ozone breaks the redox balance and aggravates oxidative damage in AR. This study suggests that inhibiting oxidative stress might be a solution for ozone-elicited detrimental effects on AR.